1997
DOI: 10.1021/bp970064m
|View full text |Cite
|
Sign up to set email alerts
|

Application of Novel Preparation Method for Surfactant-Protease Complexes Catalytically Active in Organic Media

Abstract: We have applied the newly developed method of preparing surfactant-enzyme complexes to other different enzyme sources in order to study the efficacy of this technique in the catalyzed transesterification processes. Protease from varied material sources was modified with surfactant molecules utilizing water-in-oil (W/O) emulsions, and the complex so formed proved very effective in catalyzing vinyl butyrate transesterification with benzyl alcohol in organic media. By contrast, native commercial protease and a ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…Dordick and coworkers reported that adding a large amount of KCl at the preparation stage (20) activates the catalytic activity of subtilisin Carlsberg in organic media. The effect of salts has also been observed in a surfactant-protease complex in our previous study (13). The oxidized product in the reaction medium was analyzed by direct ionization mass spectrometry (DIMS) and was identified as 2,3-diaminophenazine (M + , 210), which is the same as the reaction product catalyzed by native laccase in an aqueous buffer solution (21) (data not shown).…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Dordick and coworkers reported that adding a large amount of KCl at the preparation stage (20) activates the catalytic activity of subtilisin Carlsberg in organic media. The effect of salts has also been observed in a surfactant-protease complex in our previous study (13). The oxidized product in the reaction medium was analyzed by direct ionization mass spectrometry (DIMS) and was identified as 2,3-diaminophenazine (M + , 210), which is the same as the reaction product catalyzed by native laccase in an aqueous buffer solution (21) (data not shown).…”
Section: Resultsmentioning
confidence: 63%
“…For example, the surfactantlipase, surfactant-protease, and surfactant-peroxidase complexes that were prepared by this novel method exhibited much higher catalytic activities compared to their native powder enzymes in various anhydrous organic media (12)(13)(14). This novel preparation method can be easily applied to many enzymes.…”
mentioning
confidence: 99%
“…Our recent work was focused on the novel preparation method utilizing water-in-oil (W/O) emulsions for surfactant-enzyme complexes. It has been confirmed that the surfactant-enzyme complexation technique is feasible by employing lipase , ␣-chymotrypsin (Abe et al, 1997), various proteases (Okazaki et al, 1997b), and horseradish peroxidase as model enzymes. The resultant complexes were soluble and catalytically active in nonaqueous media.…”
Section: Introductionmentioning
confidence: 92%
“…Our recent works were focused on surfactant-enzyme complexes, which are different from ordinary surfactantcoated enzymes (Okahata and Ijiro, 1988;Goto et al, 1994) owing to the different preparation techniques Okazaki et al, 1997a). The novel preparation method utilizing W/O emulsions for surfactant-enzyme complexes has been established, and its utility has been confirmed by employing a lipase (Okazaki et al, 1997a), R-chymotrypsin (Abe et al, 1997), and other proteases (Okazaki et al, 1997b). The resultant complexes are soluble and catalytically active in nonaqueous media.…”
Section: Introductionmentioning
confidence: 99%